41Ca Concentrations in Modern Bone and Their Implications for Dating. Issue 3 (18th July 2016) - Middleton, Roy; Fink, David; Klein, Jeffrey; Sharma, Pankaj
Abstract : We have made the first measurements without pre-enrichment of 41 Ca in terrestrial rock and bone samples using accelerator mass spectrometry. Although the results in tufa deposits from Egypt are in good agreement with the saturation value of 8×10 -15 predicted by Raisbeck and Yiou (1979), the average 41 Ca: 40 Ca ratio of 2×10 -15 (range: 0.6 to 4.2×10 -15 ) that we measure in modern bone is an order of magnitude lower than that obtained previously by Henning, et al (1987) on a cow bone that was measured using AMS following isotope enrichment. The low value and the variability (more than a factor of seven) of the 41 Ca: 40 Ca ratio in modern bone make the possibility of dating bones using 41 Ca unlikely.